Dihydroquercetin Activates AMPK/Nrf2/HO-1 Signaling in Macrophages and Attenuates Inflammation in LPS-Induced Endotoxemic Mice - Lei, Liming; Chai, Yunfei; Lin, Haoming; Chen, Chunbo; Zhao, Mingyi; Xiong, Weiping; Zhuang, Jian; Fan, Xiaoping (Frontiers in Pharmacology, 2020)
Dihydroquercetin (DHQ) is a flavonoid compound known for its anti-oxidant effects. Oxidative stress plays a dominant role in regulating the pathways associated with systemic inflammatory immune activation during endotoxemia. Whether and how DHQ regulates inflammatory responses in endotoxemia remains elusive. Here we show DHQ pretreatment effectively reduced the Ten-day mortality in bacterial endotoxin lipopolyssacharide (LPS)-challenged mice, suppressing LPS-induced inflammatory responses reflected by impaired production of tumor necrosis factor α (TNF-α) and IL-6 in the serum of mice. In Raw 264.7 cells, DHQ pretreatment significantly inhibited the transcriptional upregulation of TNF-α, IFN-γ, IL-10 and TLR-4 after LPS stimulation. Additionally, knockdown of heme oxygenase-1 (HO-1), one of the most important DHQ induced antioxidant genes, cancelled the inhibition of DHQ treatment on LPS induced TNF-α, IFN-γ production. Nuclear factor erythroid 2-related factor 2 (Nrf2) expression and AMP-activated protein kinase (AMPK) phosphorylation were both enhanced by DHQ in Raw 264.7 cells, indicating a DHQ induced AMPK/Nfr2/HO-1 signal axis. In conclusion, DHQ pretreatment could protect mice against the inflammation and mortality associated with endotoxemia.